Exhibiting the past : Caspar Reuvens and the museums of antiquities in Europe, 1800-1840 - Hoijtink, Mirjam, (Papers on archaeology of the Leiden Museum of Antiquities ;)
In the first decades of the 19th century the exhibition of antiquity in museums reflected a universal history of civilization, in which the idea of cross-cultural influences dominated. Hindu-buddhist civilization of 13th century Java was easily connected to that of classical Greece, and Indian Hindu-depictions were playfully related to those of Egyptian Pharaonic time. This book shows how antiquity, during and just after the Napoleonic era formed a statement in a changing world at the dawn of nationalism. The main character is the first professor of Archaeology Caspar Reuvens, director of the Museum of Antiquity in Leiden, the Netherlands (1818-1835). It emphasis on his forming years in Paris and Germany, his many travels to London, and his plans for a journey to Rome. Beside, it sheds new light on the radically changing canon of antique sculpture in a nervous Europe, that soon would be falling apart in nation states.